2019
DOI: 10.1002/ep.13269
|View full text |Cite
|
Sign up to set email alerts
|

Performance, emission, energy, and exergy analysis of CI engine using Kaner seed pyrolysis oil blended diesel

Abstract: This work reports the engine performance, emission parameters, and energy‐exergy characteristics of a twin cylinder four‐stroke CI engine fueled with Diesel blended Kaner seed pyrolysis oil (KSPO). KSPO is obtained by the thermal pyrolysis of Kaner (Thevetia peruviana) seed at 600°C in a batch reactor and mixed with diesel in the ratio of 5, 10, 15, and 20%, to use in the engine. Brake thermal efficiency is marginally higher and brake specific fuel consumption is comparatively lower for KSPO‐diesel blend as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For energy analysis, emission gas concentration (ppm) is changed to specific fuel consumption (g/kWh). The equations are as follows (Ahmadi et al , 2021; Gouda et al , 2019; Soudagar et al , 2020): …”
Section: Methodology Followed For Planning the Experimentsmentioning
confidence: 99%
“…For energy analysis, emission gas concentration (ppm) is changed to specific fuel consumption (g/kWh). The equations are as follows (Ahmadi et al , 2021; Gouda et al , 2019; Soudagar et al , 2020): …”
Section: Methodology Followed For Planning the Experimentsmentioning
confidence: 99%
“…resultant from high viscosity and poor volatility. 54,61,62 From Figure 9, it is found that the maximum BSCO is estimated for the C30J70 as 31.82 g/kWh, which is 67.50%, 37.80%, 80%, 26.04%,47.47%, and 82.10% higher than diesel, C50J50, C70J30, C30J70 + 10%DEE, C50J50 + 10%DEE, and C70J30 + 10%DEE, respectively. Also, at full load conditions, the maximum BSCO is found for C30J70 as 15.93 g/kWh which is 44.34%, 31.35%, 62.47%, 30.29%, 55.80% and 71.99% higher than diesel, C50J50, C70J30, C30J70 + 10%DEE, C50J50 + 10%DEE and C70J30 + 10%DEE, respectively.…”
Section: In-cylinder Pressurementioning
confidence: 99%
“…It was obtained that the loss in the exhaust was decreased by 1.8% for the WCO10, 3.7% for the WCO20 and 4.5% for the WCO30 of fuel blend. Gouda et al [25] analyzed the CI engine by using energy, exergy, emission and performance analyses. It was found that the standard diesel fuel emissions were higher than CO emissions of KSPO diesel.…”
mentioning
confidence: 99%